Adopting particle-packing method to develop high strength palm oil clinker concrete - Abutaha, Fuad; Razak, Hashim Abdul; Ibrahim, Hussein Adebayo; Ghayeb, Haider Hamad (Elsevier, 2018)
Utilization of locally available waste and by-product to replace conventional concrete materials has gained considerable attention over the past two decades. This study is a part of an extensive research program on the characteristics of palm oil clinker (POC) incorporated concrete. In this study, experimental investigation was carried out on incorporating POC as aggregates and filler material in the production of high strength concrete (HSC). Crushed POC were used as partial and full replacement of natural aggregates i.e. fine and coarse. Palm oil clinker powder (POCP) was then incorporated to fill the voids present on the surface of POC particles, while maintaining the other mix constituents. Fresh and hardened properties of the POC concrete with and without POCP were investigated. Substituting coarse aggregate with POC negatively affected the concrete fresh and hardened properties due to POC porous nature. However, the results of the study revealed that incorporating additional POCP as filler material by adopting Particle-Packing (PP) method improved the engineering properties of POC concrete. Therefore, there is a potential towards utilization of POC for many practical construction applications. POC being an environmentally-friendly and a low-cost aggregate can serve as a normal aggregate alternative for future use.